Efektivitas Penggunaan Layanan Fitur Syariah Aplikasi Pospay Pada Pengguna Di Surabaya - Rosadi, Danang; Indrarini, Rachma (Perbanas Journal of Islamic Economics and Business, 2025)
This study aims to analyze the effectiveness of the use of sharia feature services in the Pospayapplication by users in Surabaya. The sharia feature on Pospay is an innovation of PT Pos Indonesia(Persero) in providing sharia services. The research method used is qualitative based with aphenomenological approach. Data collection techniques were conducted through interviews andobservations of active users of sharia features in Surabaya, application informatics technicians, andrepresentatives of the Surabaya Post Office. Data analysis used the Miles and Huberman model withthe stages of open coding, axial coding, and selective coding. The results showed that the shariafeatures in Pospay are considered effective in supporting users' sharia needs activities. Users feelhelped because services can be accessed easily, safely, and in accordance with sharia principles.However, there are some weaknesses such as the lack of socialization, limited sharia institutionpartners, technical constraints when the network is unstable. These findings provide a real picture ofthe dynamics of the use of application-based sharia services, especially in the context of digitalplatforms owned by non-bank SOEs which are still rarely studied. Solutions that can be done areincreased promotion, expansion of cooperation with Islamic financial institutions, strengthening thetechnical side of the application. This research is expected to contribute to the development of Islamicfintech in Indonesia.